Nano-ZnO film preparation at low temperature and the optical indices calculation - 杨爱玲 包西昌 李顺嫔 阳仁强 王婷 王玉金 孙亮 (Optoelectronics letters, 2014)
The refractive indices of thin films based on Kramers-Kronig theory are corrected. And the correction theory is used to determine the optical indices of nano-ZnO thin films prepared by low temperature sol-gel method. The calculated results indicate that in the visible （Vis） range, the refractive indices of nano-ZnO thin films exhibit a slight abnormal dispersion, while in the ultraviolet （UV） region, the refractive indices increase with wavelengths increasing （normal dispersion）. But the refractive indices show complex change near the absorption edge. The maximum refractive index （1.95） of nano-ZnO thin films within UV range at low temperature annealing is much lower than that of the films annealed at high temperature. The absorption and refractive indices are closely related to the defects in nano-ZnO thin films.